Morphometric Characteristics of Freshwater Shrimp in Lotic and Lentic Habitats of Ogan Ilir Regency, South Sumatra - Stilaf Terbit Galih Walsandy; Arum Setiawan; Kodri Madang (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the length–weight relationship and morphometric variation of three freshwater shrimp species from lotic and lentic habitats in Ogan Ilir Regency, South Sumatra, Indonesia. The study was conducted from November 2025 to May 2026 using purposive sampling at six aquatic stations, comprising three lotic and three lentic habitats. A total of 300 shrimp specimens were collected using baited traps (bubu) and hand nets. The observed parameters included total length and body weight. Length–weight relationships were analyzed using the allometric equation W = aLᵇ, whereas morphometric variation was evaluated using Principal Component Analysis (PCA). The results showed that Palaemon carcinus exhibited positive allometric growth in both lotic (b = 5.805) and lentic habitats (b = 6.963). Similarly, Macrobrachium rosenbergii showed positive allometric growth in lotic (b = 8.230) and lentic habitats (b = 3.973). In contrast, Macrobrachium nipponense demonstrated positive allometric growth in lotic habitats (b = 4.960) but negative allometric growth in lentic habitats (b = 0.899). PCA revealed that most morphometric variation was explained by the first principal component (PC1), indicating a strong association between total length and body weight. These findings suggest that habitat type, particularly differences between lotic and lentic aquatic systems, influences growth patterns and morphometric variation in freshwater shrimps in South Sumatra.